ANALISIS PENERAPAN SISTEM SAFETY PERMIT DI UNIT PLTU TELUK BALIKPAPAN - Febriyani, Dini (IDENTIFIKASI, 2020)
This research was conducted at PLTU Teluk Balikpapan. The research objective was to analyze the implementation of a safety permit based on the reference standards Guidelines on Permit to Work System-Oil and Gas Producers 2003. This type of research is descriptive-qualitative. The results of the research on the safety permit procedure of PLTU Balikpapan have the conformity of 89% with the Guidelines on Permit to Work System-Oil and Gas Producers 2003. The remaining 15% is in the form of non-conformities at the preparation stage, namely in the isolation stage at PLTU Teluk Balikpapan using Log Out Tag Out (LOTO ) by installing locks and warning signs on equipment in the form of barricades around the work area. Apart from that, in the process stage, the display of permit on the information board or wallpaper for a safety permit is not made. In conclusion, the tagging system and key installation have been implemented, but there is only 1 (one) key provided and held by the operator, so accessing the equipment/system with multiple work permits will experience problems. other than that, the display of permit on the information board is not made.